183 Antidepressant Adherence and Alternative Future Options in Pacific Islander Youth. (April 2020) - Portman, Will; Wang, Dawei; Ruege, Andrew
Abstract: Objectives: To investigate the current response to psychopharmacology and transcranial magnetic stimulation (TMS) in Pacific Islander adolescents with Major Depressive Disorder (MDD). BACKGROUND: 40-60% of youth with Major Depressive Disorder (MDD) have a limited response to current treatment protocols and require either (a) medications with a wider side effect profile, (b) intensive psychosocial programs that interfere with school, and/or (c) publicly spurned options (electroconvulsive therapy). Such results are tempered further when working with Pacific Islanders, as such youth and families have shown in multiple studies. The aversion to such standard treatment is concerning, as Native Hawaiian adolescents have a higher risk of suicide than other adolescents in Hawaii (12.9/100, 000 youth per year). With this in mind, the investigators wondered how a novel, non-pharmacological approach to depression treatment in children, transcranial magnetic stimulation (TMS), would fair. METHODS: 2 literature searches (utilizing Pubmed, Ovid, Google Scholar, and OneSearch) were conducted on 6/10/19: 1 investigating rTMS in adolescent depression, the other researching rTMS in depression in Native Hawaiian or other Pacific Islander youth. RESULTS: At this point in time, 10 studies exist testing TMS' effects in children and adolescents with treatment refractory depression. 9 of said studies were open-label trials; 1 was a small (n=2) RCT (with both patients randomized to the active arm). Of those evaluating depression severity through Children's Depression Rating Scale-revised ("CDRS-R") scores, 100% of the trials (8/8) displayed a statistically significant improvement. None of the trials of the 1st series of searches nor the entirety of the 2nd series yielded information as to how TMS fairs in Native Hawaiian or other Pacific Islander youth. CONCLUSIONS: No studies exist that can verify the efficacy of TMS in youth, of Oceanic origin or otherwise, with the same degree of scrutiny as currently done in adults. Therefore, our group is engaging in a pilot study to evaluate the performance of TMS for the treatment of MDD in Native Hawaiian and other Pacific Islander adolescents aged 12-17; we are planning on then progressing on to a sham-controlled RCT in a larger sample size of the same population to test its efficacy in not just Pacific Islanders, but all youth. Funding Acknowledgements: no funding